Crime Prevention Policies in Comparative Perspective. - Crawford, Adam (Willan Pub., 2009)
The book brings together a collection of leading international experts to explore the lessons learnt through implementation and the future directions crime prevention policies. Many of the contributors have been closely involved in crime prevention and community safety policy and research in different countries over a number of years. As such, they are well placed to reflect upon developmental trajectories and the direction of change over the last quarter of a century, as well as to draw out the underlying influences that have shaped such changes.